Lightweight Encryption Schemes for the Internet of Things: A Review - Luangoudom, Sonxay; Tran, Duc; Nguyen, Linh Giang (Old Journal, 2020)
Nowadays, Internet of Things (IoT) enables many low resources and constrained devices to communicate, data analysis, control process and make decision in the communication network. Lightweight encryption schemes can be implemented in resource-constrained IoT devices with different cryptography primitives. However, in the heterogeneous environments for IoT, there are many challenges and issues for lightweight encryption suchlike power consumption, memory space, performance cost, and security. In this paper, we present and discuss performance of lightweight encryption algorithms integrated on IoT devices which are limited in resources, power and processing capacity and criteria to choose appropriate algorithm for each specific IoT application.